Knowledge, Attitude and Practice on Biologicals and Biosimilars among Clinicians in Radiotherapy Department - Manju Agrawal; Shantanu Mishra; Geetika Nayak; Divish Aggarwal; Usha Joshi (Research Center for Rational Use of Drugs (RCRUD), 2023)
Background: The decoding of human genome helped to design pharmacological agents like Biologicals and Biosimilars which can target the affected etiological aberrations. Biological agents are large complex molecules produced by recombinant techniques in a living system for therapeutic or diagnostic uses and have revolutionized treatment of many diseases. Patent expiry of Biologicals has led to the development of Biosimilars which are similar in efficacy & safety and have no clinically meaningful differences, but are not identical to Biologicals and undergo fewer clinical trials than their reference biologicals. Clinicians' in- depth knowledge of these agents is important to optimize the use of cost-effective & easily accessible options. Methods: This is a cross sectional observational study conducted between Feb-March 2020 in Radiotherapy/Chemotherapy Oncology Department of Dr B.R.A.M. Hospital & Pt. J. N. M. Medical College, Raipur, Chhattisgarh, using a self-administered, structured questionnaire consisting of 15-question among 30 clinicians prescribing Biologicals and Biosimilars. Results: 83.3% of clinicians were familiar with the term 'Biologicals' & 'Biosimilars'. 60% believed that Biosimilars are same as Generic Medicines and have the same potency as Biologicals. 53% assumed that Biologicals & Biosimilars can be switched. 50% were able to explain the difference or similarity between Biologicals and Biosimilars. Conclusion: The findings reveal that the clinicians had good knowledge about Biologicals and Biosimilars but lacked application of this knowledge in clinical practice. This highlights a need for regular educational initiative to reduce the knowledge deficit & its application in clinical practice. Further, there must be a National Treatment Guidelines on use of Biologicals  and Biosimilars.